1999
DOI: 10.1001/jama.281.21.2013
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Energy Undernutrition Among Elderly Hospitalized Patients

Abstract: Throughout their hospitalization, many elderly patients were maintained on nutrient intakes far less than their estimated maintenance energy requirements, which may contribute to an increased risk of mortality. Given the difficulties reversing established nutritional deficits in the elderly, greater efforts should be made to prevent the development of such deficits during hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
1
15

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(110 citation statements)
references
References 23 publications
1
90
1
15
Order By: Relevance
“…Since continued sub-91 optimal food intake can eventually lead to deterioration of nutritional status, it is 92 important to evaluate the effect of poor food intake on health-related outcomes. Two 93 studies have reported the link between poor food intake during hospitalisation and 94 mortality [6,8], however there is no published evidence regarding the association 95 between poor food intake and readmissions and/or LOS.…”
mentioning
confidence: 99%
“…Since continued sub-91 optimal food intake can eventually lead to deterioration of nutritional status, it is 92 important to evaluate the effect of poor food intake on health-related outcomes. Two 93 studies have reported the link between poor food intake during hospitalisation and 94 mortality [6,8], however there is no published evidence regarding the association 95 between poor food intake and readmissions and/or LOS.…”
mentioning
confidence: 99%
“…O elevado índice de antibióticos prescritos resulta provavelmente do fato de doenças infecciosas estarem presentes entre a população estudada. Este achado está em consonância com outros trabalhos publicados, que mostram a prevalência de doenças infecciosas entre os idosos, inclusive por pneumonias 18,32,33,34 , sendo, sobretudo, relacionada à alta frequência de mortalidade, especialmente em quadros de desnutrição 35,36 .…”
Section: Doenças Motivadoras Da Internaçãounclassified
“…O termo desnutrição protéico-calórica engloba dois tipos 7 : marasmo (má nutrição quantitativa, hipoalimentação global ou calórica, subnutrição), que se caracteriza pela falta de calorias e proteínas; Kwashiokor (má nutrição qualitativa, predominantemente protéica), em que ocorrem distúrbios metabólicos diversos em estados mais graves. Além do número excessivo de óbitos que vem causando a cada ano, a desnutrição protéi-co-calórica agrava as doenças em atividade, torna maior a susceptibilidade a infecções e aumenta os riscos para outras morbidades, reduzindo consideravelmente a qualidade de vida 8,9 .…”
Section: Introductionunclassified